(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Tourism is not only financial and economic stability, but also a bridge of interregional relations. Tourism development should undoubtedly become a leading factor in the preservation of biological diversity. Ecosystem of tourist destinations requires only careful attitude from local and foreign tourists. A certain part of the income received from receiving and providing services to the flow of tourists is directed to the protection of the ecosystem. The mission of the concept of sustainable tourism and the implementation of the priority tasks formed within it will ultimately be the basis for consistently increasing the pace of socio-economic development. International organizations operating in the field of tourism, interregional associations, national ministries and agencies, regional management bodies, business entities are responsible for the full implementation of the same goals and tasks in their integration relations and business relations. This article describes in detail the directions of tourism related to the economy, the steps in their development, projects and, in a word, the importance of tourism in the development of the country. Examples of scientific research and statistics of world scientists are also given in the given opinions.